Distance learning, technological devices, lifestyle and behavior of children and their family during the COVID-19 lockdown in Lombardy: a survey - Marina Picca; Paola Manzoni; Gregorio Paolo Milani; Susanna Mantovani; Claudio Cravidi; Danila Mariani; Angela Mezzopane; Roberto Marinello; Chiara Bove; Paolo Ferri; Marina Macchi; Carlo Agostoni (BMC, 2021)
Abstract Background The COVID-19 pandemic and the subsequent national lockdowns, school closures and distance learning may have had both negative and positive effects on physical and mental health of children. Methods A cross-sectional study was conducted on a large group of children between 1 and 10 years old in Lombardy, Italy (n = 3392). Their parents filled in a survey answering single or multiple-choice questions about their offspring's behavior changes (including sleep, dietary habits, emotional disturbances), relationship with siblings, parents and peers, the use of digital technologies, and distance learning experience during the lockdown. Results Parents reported lifestyles and emotional alterations during the lockdown. The modifications of family relationships, parents' remote working, and screen time were associated with sleep, emotional and behavioral modifications. Distance learning was overall considered adequate. Conclusions This study reported the most updated data on the effects of COVID-19 pandemic lockdown on children between 1 and 10 years of age in a large sample of Italian schoolchildren. The results of this study point out that pediatricians and authorities should support relationships within families during the COVID-19 pandemic. Parents' remote working might play an important role for this purpose.